Soil Characteristics, Evaluation of land capability classification and its Prediction for Proper Land use and Soil Conservation Measures in the Upper Damodar Valley Catchment Area - Sarkar, A.K. (Journal of Soil and Water Conservation, 2022)
The Damodar Valley Corporation, the pioneer river valley project in India has constructed 4 multipurpose dams in the Chotanagpur plateau region of Bihar with a view to tame the turbulent Damodar and her tributaries which were causing great devastating flood in the deltaic West Bangal from time immemorial. The watershed of 4 reservoirs which is known as Upper Damodar Catchment suffers from various sorts of erosion, poor fertility and misman gement which if not tackled on top priority basis, will jeoparadise the longivity of the dams, agricultural production and the last but not the least the economic condition of this tribal area.